Embodiment of intersubjective time: relational dynamics as attractors in the temporal coordination of interpersonal behaviors and experiences - Laroche, Julien; Berardi, Anna Maria; Brangier, Eric (Frontiers in Psychology, 2014)
This paper addresses the issue of «being together», and more specifically the issue of « being together in time ». We provide with an integrative framework that is inspired by phenomenology, the enactive approach and dynamical complex systems. To do so, we first define embodiment as a living and lived phenomenon that emerges from agent-world coupling. We then show that embodiment is essentially dynamical and therefore we describe experiential, behavioral and brain dynamics. Both lived temporality and the temporality of the living appear to be complex, multiscale phenomena. Next we discuss embodied dynamics in the context of interpersonal interactions, and briefly review the empirical literature on between-persons temporal coordination. Overall, we propose that being together in time emerges from the relational dynamics of embodied interactions and their flexible co-regulation.